PENGARUH LINGKUNGAN KERJA DAN KOMUNIKASI TERHADAP DESAIN KERJA PEGAWAI YPI AL-AZHAR JAKARTA - Eko Budiyono (Jurnal Manajemen Pendidikan, 2014)
The objective of this research is to obtain information concerning effect of work environment and communication on employee's job design YPI Al-Azhar Jakarta.The research was carried out by means of survey in YPI Al-Azhar Jakarta, involving 61 employees as respondents who are selected through simple random sampling.This research finding are (1) there is a direct effect work environment on employee's job design. (2) there is a direct effect of work environment on communication. (3) there is a direct effect of communication on employee's job design.Therefore, the variation of employee's job design are effected by the variation of work environment, variation of communication, and others variation.